Manihot montana, a new species of Manihot sect. Graciles (Euphorbiaceae) from the Brazilian savannas - Da Silva, Marcos José; de Souza, Alessandro Oliveira; Alonso, Alexandre Antônio; Esser, Hans-Joachim (Phytotaxa, 2019)
Manihot montana, a new species of wild cassava, is described and illustrated based on material from the Brazilian savannas. We compared its macromorphology and leaf anatomy to M. paviifolia, the most morphologically similar species. In addition, we provide images of the new species, details on its distribution, conservation status assessment, phenology and comments on its ecology, morphological relationships and systematic position.